HOLISTIC VISION: INTEGRATIVE APPROACH IN GUIDANCE AND COUNSELING SERVICES - Hidayat, Ade (GUIDENA: Jurnal Ilmu Pendidikan, Psikologi, Bimbingan dan Konseling, 2016)
Abstract: The philosophical issues in Guidance and Counseling especially in epistemological discourse have made paradigmatic friction that pointed by some issues from therapeutic-clinical to comprehensive way with preventive development prespective approach. It was  also caused by the wider friction where quantum physic has remove classic Newtonian one, then the influence has generally removed another disciplines, where Guidance and Counseling in one of them. Through the comprehensive paradigm, Guidance dan Counseling need to take prepare the expert in order to capable to develop integrated and comprehensive thinking awareness. It means the Guidance and Counseling holistic vision is urged. Through the holistic vision, all of the competency of student is noticed integrally, such as intellectual, emotional, social, physical, artistic, creativity, ecological awareness, and spiritual competencies.